Replaying Empire: Racialized Violence, Insecure Frontiers, and Displaced Terror in Contemporary Video Games - Leonard, David J.; King, C. Richard (Ethnicity and Race in a Changing World, 2009)
In the wake of 9/11, US popular culture has played an important role in the manufacture of consent and the mediation of contradictions. In particular, video games have aff orded the production of interactive, narrative spaces for the reassertion of race, nation, and gender. Through a close reading of two video games, Gun and Ghost Recon Advanced Warfighter 2, we unpack the insecurities of empire and how racialized violence, colonial categories, and territorial claims work to resecure Whiteness, masculinity, and Americanness. Special attention is given to the militarization of video games and rhetorical struggles over the meaning of race and culture amid the ‘War on Terror’.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Beyond Hate: White Power and Popular Culture - King, C. Richard; Leonard, David J. (Cultural politics of media and popular culture, 2016)
Beyond Hate offers a critical ethnography of the virtual communities established and discursive networks activated through the online engagements of white separatists, white nationalists, and white supremacists with various popular cultural texts, including movies, music, television, sport, video games, and kitsch. Outlining the ways in which advocates of white power interpret popular cultural forms, and probing the emergent spaces of white power popular culture, it examines the paradoxical relationship that advocates of white supremacy have with popular culture, as they finding it to be an irresistible and repugnant reflection of social decay rooted in multiculturalism. Drawing on a range of new media sources, including websites, chat rooms, blogs and forums, this book explores the concerns expressed by advocates of white power, with regard to racial hierarchy and social order, the crisis of traditional American values, the perpetuation of liberal, feminist, elitist ideas, the degradation of the family and the fetishization of black men. What emerges is an understanding of the instruments of power in white supremacist discourses, in which a series of connections are drawn between popular culture, multiculturalism, sexual politics and state functions, all of which are seen to be working against white men. A richly illustrated study of the intersections of white power and popular culture in the contemporary U.S., and the use of use cyberspace by white supremacists as an imagined site of resistance, Beyond Hate will appeal to scholars of sociology and cultural studies with interests in race and ethnicity, popular culture and the discourses of the extreme right.
Keywords: 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Télé